The main results of breeding and seed production of perennial grasses on the Don area in 2010–2020 - S. A. Ignatiev; A. A. Regidin; T. V. Gryazeva; K. N. Goryunov (Зерновое хозяйство России)
The current paper has presented an overview of the work of the laboratory for breeding and seed production of perennial grasses of the ARC “Donskoy” over a ten-year period. There has been presented a brief history of the development of the laboratory from the moment of its establishment to the present day. The main purpose of the work in this period was the breeding, reproduction, introduction into production of the new alfalfa and sainfoin varieties with a wide range of resistance to various stress factors with high productivity of forage and seeds. In the collection farms of alfalfa there have been tested and agro biologically estimated more than 600 varieties from the world collection of VIR, other research institutions and local hybrids. Based on this work there have been developed an initial material with a wide variability of economically-biological useful characters using the methods of hybridization and selection. The best lines and hybrids were included in the complex hybrid populations, which became the basis for the development of the new alfalfa varieties ‘Selyanka’ (2013) and ‘Golubka’ (2019). Throughout the history of the laboratory, great attention was paid to the development of the new sainfoin varieties, as a result of which there were zoned such varieties as ‘Severokavkazky dvuukosny’ (1947), ‘Zernogradsky 2’ (1998), ‘Zernogradsky 3’ (2001), ‘Atamansky’ (2004), ‘Veles’ (2010). Over the past ten years, there were developed the sainfoin varieties ‘Sudar’ (2013) and ‘Shuravi’ (2019) protected by a patent, the varieties undergone the State Variety Testing, were included into the State List of Breeding Achievements approved for use in several regions of the Russian Federation. There has been given a brief description of the current problems of breeding and primary seed production of perennial grasses, as well as the directions of the laboratory's work to solve them. There has been presented the publication activity of the researchers of the laboratory.